Thyroid Lymphoma as a Cause of Dysphagia and Dyspnea in a Patient without Palpable Nodules or Goiter - Jarrod D. Frizzell; Brandon J. Perkins; R. Scott Morehead (Case Reports in Medicine)
Tumors originating in the neck are well-known causes of progressive dysphagia and dyspnea (including stridor), and thyroid lymphoma is an uncommon example. Physical examination provides an important first step in the evaluation of such complaints, as tumors large enough to produce such symptoms are typically considered to be palpable, if not able to be seen grossly. In this case presentation, the authors describe a nonsubsternal thyroid lymphoma measuring 3×4 cm at its largest diameter, producing dysphagia and leading to respiratory emergency, that was entirely nonpalpable to physical exam even after confirmation of its presence by computed tomography.